Un régime pragmatique de l’arrangement. L’en-deçà du public, l’au-delà du familier - Nachi, Mohamed (SocietàMutamentoPolitica, 2021)
In this paper, I propose to define the properties of a new pragmatic regime of action, which I have appointed as the « regime of the arrangement ». After a review of some work on regime of action developed from the perspective of pragmatic sociology, I underlined the importance of faces of arrangement in different areas of social life. By pointing out the semantic ambiguity of the arrangement, I have been able to identify the provisions, resources and practical modalities that allow me to consider it as a hybrid regime that is positioned beyond the familiar, but below the public.